Suffering Loves and Needs Company: Buddhist and Daoist Perspectives on the Counsellor as Companion - Cohen, Avraham; Bai, Heesoon (Canadian Journal of Counselling and Psychotherapy, 2008)
Mindful of living in a multicultural and cross-cultural society, this article introduces and presents Buddhist and Daoist philosophy, psychology, and practice along with the potential for their application in psychotherapy within the context of the theme of the psychotherapist or counsellor accompanying the suffering person. The theoretical grounding for this application is the understanding that the suffering person has an underlying need for ontological security. It is suggested that this is made possible by a twofold connection: intra-subjective connection to self through integration of emotions, thoughts, and psycho-physical states; and inter-subjective connection to others. A case is made in this article that the therapist’s mindful and energetic presence is key to the development of this connection.